2013
DOI: 10.1016/j.coastaleng.2012.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modeling of shoreline undulations part 2: Varying wave climate and comparison with observations

Abstract: a b s t r a c t a r t i c l e i n f oThe present work applies the shoreline model from part 1 to a real environment. In part 1, a numerical shoreline model which could handle the development of arbitrarily shaped shorelines was applied to consider the development of shoreline undulations on an unstable shoreline exposed to incoming waves with a directional spreading. In this paper, these findings are extended to firstly include the effect of a varying wave climate on the shoreline morphology and secondly, to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 17 publications
3
36
1
Order By: Relevance
“…Although they are the most representative of morphological processes, they are limited by the extent and frequency of available historical data. Process‐driven models characterize the dominant physical processes shaping coastlines such as gradients in longshore sediment transport (LST) (Ashton et al, , ; Ashton & Murray, , ; Arriaga et al, ; Falqués et al, ; Hanson, ; Idier et al, ; Kaergaard & Fredsoe, , ; Murray & Ashton, ), wave‐driven cross‐shore shoreline change (Yates et al, , ; Davidson et al, , ; Splinter et al, , ), beach profile response to water levels and waves (Aagaard, ; Kriebel & Dean, ; Miller & Dean, ; Larson et al, ; Patterson & Nielsen, ), and profile adjustment due to SLR (Bruun, ) without solving complex governing equations as physics‐driven models do. Process‐driven models have been proven reliable and computational inexpensive; however, they usually focus on solving a single physical process.…”
Section: Introductionmentioning
confidence: 99%
“…Although they are the most representative of morphological processes, they are limited by the extent and frequency of available historical data. Process‐driven models characterize the dominant physical processes shaping coastlines such as gradients in longshore sediment transport (LST) (Ashton et al, , ; Ashton & Murray, , ; Arriaga et al, ; Falqués et al, ; Hanson, ; Idier et al, ; Kaergaard & Fredsoe, , ; Murray & Ashton, ), wave‐driven cross‐shore shoreline change (Yates et al, , ; Davidson et al, , ; Splinter et al, , ), beach profile response to water levels and waves (Aagaard, ; Kriebel & Dean, ; Miller & Dean, ; Larson et al, ; Patterson & Nielsen, ), and profile adjustment due to SLR (Bruun, ) without solving complex governing equations as physics‐driven models do. Process‐driven models have been proven reliable and computational inexpensive; however, they usually focus on solving a single physical process.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, after Ashton and Murray [], an increase of wave height H and period T leads to an increase of the diffusional time scale ( H12/5T1/5), i.e., speeds up the sand waves development in case of high‐angle waves. Kaergaard and Fredsoe [, ] investigated the effect of wave directional spreading, the closure depth D c , and the shoreface steepness and showed that sand wave wavelength increases with increasing directional spreading and D c , while it decreases with increasing shoreface steepness. However, these studies did not investigate the effect of these parameters on the instability onset.…”
Section: Introductionmentioning
confidence: 99%
“…Third, the Atlantic coast of Africa is exposed to larger wave height and period than the ones used in the model analysis. Forth, as suggested by Kaergaard and Fredsoe (2013b), the smallest waves within the wave spectrum arrive with a larger obliquity at the coast and can contribute to the shoreline instability even more than the dominant waves. Finally, the sensitivity of the ratio results should be analysed taking into account the data quality.…”
Section: Shoreline Wavelength Wave and Morphologymentioning
confidence: 99%
“…The mean wave approach is quite oblique there, from the NW, but the angle with the shore normal is nearly at the threshold of instability. Kaergaard and Fredsoe (2013b) have done the corresponding stability analysis and concluded that only if the large storm waves were excluded from the wave climate the coastline would be unstable and shoreline sandwaves with the observed wavelength would emerge. Kaergaard et al (2012) investigated also the cross-shore extent of coastline undulations on a site located on the West coast of Denmark, based on specific bathymetric surveys providing temporal and spatial data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation